Penerapan Sistem Pakar Forward Chaining Dalam Menentukan Bakat Minat Siswa - Ade Tiara Susilawati; Arbansyah Arbansyah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Education plays a crucial role in students' development, particularly in understanding their talents and interests. SDN 037 Kota Bangun faces challenges in efficiently and accurately determining the talents and interests of its students. In this community service initiative, an expert system using the Forward Chaining method is employed to address this issue. The service methodology includes problem identification, the design of a Visual Basic-based expert system, student training, and result evaluation. The expert system utilizes identified criteria through Forward Chaining to provide recommendations for students' talents and interests. Evaluation indicates positive feedback regarding understanding and ease of system use. The results of the community service show the positive contribution of the expert system in expediting the determination of students' talents and interests. However, further development is needed to enhance the system's accuracy, especially in handling students with more than one talent. This implementation is considered a positive initial step with potential for further advancement.